(untitled) (Conferencea, 2024)
I. Yusupov is a wordsmith who opened the way for the development of the poem genre in Karakalpak literature. The poet’s creations in this genre are appreciated by scientists, and they note that they contributed to the enrichment of the branch poem in terms of genre and idea-thematic. The well-known scientist G. Esemuratov writes about the poet’s poems: "I. Yusupov’s poetry is a proof of the growth of the attitude towards human and the demands placed on him. Poems about the urgent problems of our modern life made from the poetic inspiration are the result of much thought and research. In them, it is often noticeable that the plot and the composition are inexplicably combined. The story doesn’t fall apart as if it were sewn with lines", [1. 111] – she evaluates. In 2019, K. Mambetov defended a dissertation on the topic «I.YUsupov poemalarınıń janrlıq ózgeshelikleri» ("Genre features of I. Yusupov’s poems") [2]. This scientific source is very valuable for us to distinguish the poet’s poems from their genre and analyze symbolic and metaphorical descriptions.